CHO Cells Adapted to Inorganic Phosphate Limitation Show Higher Growth and Higher Pyruvate Carboxylase Flux in Phosphate Replete Conditions - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology progress, 2017)
Inorganic phosphate (P-i) is an essential ion involved in diverse cellular processes including metabolism. Changes in cellular metabolism upon long term adaptation to P-i limitation have been reported in E. coli. Given the essential role of P-i, adaptation to P-i limitation may also result in metabolic changes in animal cells. In this study, we have adapted CHO cells producing recombinant IgG to limiting P-i conditions for 75 days. Not surprisingly, adapted cells showed better survival under P-i limitation. Here, we report the finding that such cells also showed better growth characteristics compared to control in batch culture replete with P-i ( higher peak density and integral viable cell density), accompanied by a lower specific oxygen uptake rate and cytochrome oxidase activity towards the end of exponential phase. Surprisingly, the adapted cells grew to a lower peak density under glucose limitation. This suggests long term P-i limitation may lead to selection for an altered metabolism with higher dependence on glucose availability for biomass assimilation compared to control. Steady state U-C-13 glucose labeling experiments suggest that adapted cells have a higher pyruvate carboxylase flux. Consistent with this observation, supplementation with aspartate abolished the peak density difference whereas supplementation with serine did not abolish the difference. This supports the hypothesis that cell growth in the adapted culture might be higher due to a higher pyruvate carboxylase flux. Decreased fitness under carbon limitation and mutations in the sucABCD operon has been previously reported in E. coli upon long term adaptation to P-i limitation, suggestive of a similarity in cellular response among such diverse species. (C) 2017 American Institute of Chemical Engineers

Circulatory levels of lysophosphatidylcholine species in obese adolescents: Findings from cross-sectional and prospective lipidomics analyses - Sharma, Sapna; Subrahmanyam, Yalamanchili Venkata; Ranjani, Harish; Sidra, Sidra; Parmar, Dharmeshkumar; Vadivel, Sangeetha; Kannan, Shanthini; Grallert, Harald; Usharani, Dandamudi; Anjana, Ranjit Mohan; Balasubramanyam, Muthuswamy; Mohan, Viswanathan; et al. (NUTRITION METABOLISM AND CARDIOVASCULAR DISEASES, 2024)
Keywords: Adolescent obesity; Asian Indians; biomarker; Lipidomics; Lysophosphatidyl- choline